EFFECTIVITY OF EXTRACT LEAF, FRUIT, ROOT MANGROVE Avecennia marina ON Aedes aegypti - Eriani, Eti; Effendi, Irwan; Yoswaty, Dessy (Asian Journal of Aquatic Sciences, 2019)
Inhibiting the life of the Aedes aegypti mosquito is the mian way that is done to eradicate DBF, which is popularly done by chemically synthetic insecticides can be used air pollution and poisoning of humans so it needs safer natural incecticides such as compounds derived from mangrove plants. Mangrove Avecennia marina contains saponis, flavonoids, and alkaloids can act as stomach poisons resulting in larval death. The study was conducted in Februari-Maret 2019. The purpose of the study was to deteremine the efectiveness of extracts of leaves, fruit Avecennia marina mangrove root that quickly inhibit the growth of Aedes aegypyi larvae. The method used was the experimental method, the location of the research sample taking in Kayu Ara Village, Siak Riau Province. Results showed the mangrove leaves at a concentration of 12% mosquito larvae deaths reached 99 tails in the 120th minute, results showed the mangrove fruit at a concentration of 12% mosquito larvae deaths reached 96 tails in the 120th minute, Results showed the mangrove root at a concentration of 12% mosquito larvae deaths reached 85 tails in the 120th minute, analyzed using probit analysis to obtain LC50 (Lethal Concentration 50) and LT50 (Lethal Time 50) values. The LC50 probit analysis velue is estimate leaves 2.721, estimate fruit 1.584 dan estimate root 1,232. Whereas at LT50 estimate leaves 2.841, fruit 1.579, root 1.115.